EMG patterns in abnormal involuntary movements induced by neuroleptics. - Bathien, N (1984)
Electromyographic (EMG) activity of abnormal involuntary movements and their modifications after Piribedil, a dopaminergic agonist, were analysed in patients presenting with tremor or tardive dyskinesia induced by treatment with neuroleptics. Quantitative analysis of EMG bursts and of their phase relationships with bursts of antagonist muscles revealed differences between tremor and tardive dyskinesia; three separate EMG types of the latter were found. In tremor, EMG activity was coordinated between agonists and antagonists. Length and frequency of bursts are characteristic. In tardive dyskinesia, phase histograms of antagonist muscle bursts showed an absence of reciprocal organisation of EMG activity. This activity was made up of either rhythmical bursts (type I and II according to the frequency) or irregular discharges (type III). Piribedil decreased tremor but facilitated EMG activity in tardive dyskinesia. These results give an objective measurement or classification of tremor and tardive dyskinesia induced by neuroleptics.